1922
DOI: 10.1001/archneurpsyc.1922.02190130062009
|View full text |Cite
|
Sign up to set email alerts
|

Statistics of Multiple Sclerosis

Abstract: This study is based on the records of 1,970 cases of multiple sclerosis. Of the total, 1,773 represent cases culled from literature and 197 those whose records I have personally studied. Of the latter, fifty-five are from the Vanderbilt Clinic, ninety-three from the Mount Sinai Hospital and forty-nine from the Montefiore Hospital. The object of the investigation was to determine the comparative incidence of the disease in the United States and Europe, the ages (including the ages of onset), average duration, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

1968
1968
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 9 publications
0
15
0
Order By: Relevance
“…Despite this, however, men have a lower threshold of actual environmental exposure for the disease to develop than women. Such a circumstance might explain why the earliest reports of MS were often in men [2] , [93] and why a 1922 study reported that of 363 MS patients from the United States and of 1,142 cases from Europe, approximately 58% (in both regions separately) were men [94] . Moreover, it can be shown that, at a minimum, there must have been a 32% increase in the prevalence of MS in Canada over the 35 year interval of study.…”
Section: Results and Methodsmentioning
confidence: 99%
“…Despite this, however, men have a lower threshold of actual environmental exposure for the disease to develop than women. Such a circumstance might explain why the earliest reports of MS were often in men [2] , [93] and why a 1922 study reported that of 363 MS patients from the United States and of 1,142 cases from Europe, approximately 58% (in both regions separately) were men [94] . Moreover, it can be shown that, at a minimum, there must have been a 32% increase in the prevalence of MS in Canada over the 35 year interval of study.…”
Section: Results and Methodsmentioning
confidence: 99%
“…At the beginning of the 20th century, however, the sex ratio was estimated to be equal or even reversed [5]. Some earlier data series [1,[6][7][8][9][10][11][12][13] that illustrate the evidence of pioneer scholars are depicted in Table 1. Counterevidence first arose from two epidemiological prevalence studies in the 1920s, one of them by Bing in Switzerland [1,6,14] and the other by Allison in North Wales [13].…”
Section: Historical Perspectivesmentioning
confidence: 99%
“…Moreover, to achieve ( F:M ) sex ratios of the magnitudes observed, requires that the difference in threshold be small ( Figure 3 ). By contrast, the circumstances of Figures 1D, 2D & 4A–4D (i.e., c < d ≤ 1), result in a continuously increasing ( F:M ) sex ratio with increasing exposure over most (or all) of the response curves, it easily accounts for the magnitudes of the observed ( F:M ) sex ratios and, in Figures 1D & 4A–D , it could also account for the observation [39], at an earlier point in the history of MS, that: …”
Section: Methodsmentioning
confidence: 95%
“…Therefore, the only circumstances for which it is possible that: ( Zw 2 ≤ Zm 2 ), are also those for which: ( p ≥ p ′ 2 ≥ 0.74). In addition, again considering the implications of Equation 1a , the only circumstances in which the ( F:M ) sex ratio can increase over time, is for the ratio ( Zw / Zm ) also to increase over time, which, in turn, requires that: ( Zw < Zm ) during any Time Period for which { p ≥ p ′ } – a circumstance that would pertain to every Time Period represented by the Canadian data [7] and, in fact, would pertain to all observations throughout the history of MS, including a time when the proportion of men among MS patients was reported to exceed that of women [39]. Thus, in the circumstance that: { p ≥ p ′ }, throughout the history of MS, including currently, susceptible men would be envisioned to have a greater penetrance for MS than susceptible women .…”
Section: Methodsmentioning
confidence: 99%